Ocular Surface Displacement with and without Contact Lenses during Non-Contact Tonometry - Rimayanti, Ulfah (Public Library of Science, 2014)
PURPOSE: To evaluate the displacement of the central ocular surface during non-contact tonometry with and without soft contact lenses and determine the factors associated with the displacement of the central ocular surface and intraocular pressure (IOP) reading changes caused by wearing soft contact lenses (CLs). METHODS: One eye each in 21 subjects was studied. The cornea was photographed using a high-speed camera at 5,000 frames/sec during non-contact tonometry without contact lenses (NCL), with -5.0 diopters (D), -0.5 D and +5.0 D CL. The displacement of the ocular surface and the factors affecting displacement at the IOP reading and maximum displacement time were investigated. RESULTS: The IOP readings while wearing +5 D CL were significantly higher than those obtained while wearing -5 D CL. The ocular surface displacement between +5 D CL and other groups were significantly different. A significant positive correlation was found between the ocular surface displacement of subjects at the IOP reading time and the IOP obtained with the non-contact tonometer. A significant negative correlation was found between the ocular surface curvature and the IOP obtained using the non-contact tonometer. The radius of curvature of the ocular surface affected the displacement during the IOP reading and maximum displacement time. CONCLUSIONS: Our results indicate that soft contact lens use changes the ocular surface behavior and IOP readings during non-contact tonometry. The radius of curvature of the eye affects the ocular surface displacement and IOP readings in this situation.